Battery storage systems integrated renewable energy sources: A biblio metric analysis towards future directions. (March 2021) - Wali, Safat Bin; Hannan, M.A.; Reza, M.S.; Ker, Pin Jern; Begum, R.A.; Rahman, M.S. Abd; Mansor, M.
Highlights: BESS and RES integration have fueled a great deal of RE developments. A historical overview and analysis of BESS integrated RES has been reviewed. Top 100 most cited articles are reviewed under some predetermined condition. This survey has exhibited a lively and developing BESS-RES field of research. Analyzing highly cited articles assist to identify future research on BESS and RES integration and advancements. Abstract: During the previous 10 years, numerous significant advances have been made in battery energy storage system (BESS) and renewable energy sources (RESs) integration and development that have fueled a great deal of investigation and further developments. A historical overview and analysis in the field of BESS as a form of RE integration has been provided in this review. A selection of the top-cited articles in the field of BESS integrated RESs is conducted through the Scopus database under some predetermined condition. The searches on the Scopus database were conducted in the third week of December 2020. Most of the articles contain experimental setup and algorithm development (50%) whereas 29.17% of articles are survey-based articles. The top-cited articles are published in 32 different journals and have 28 different countries of origin. This survey has exhibited that BESS integrated RESs integration is a lively and developing field of research. It is hoped that identifying and analyzing the highly cited articles will assist to identify future research in the field of BESS and RESs integration and advancements.